2008
DOI: 10.1590/s1516-31802008000300005
|View full text |Cite
|
Sign up to set email alerts
|

Marginal grafts increase early mortality in liver transplantation

Abstract: CONTEXT AND OBJECTIVE: Expanded donor criteria (marginal) grafts are an important solution for organ shortage. Nevertheless, they raise an ethical dilemma because they may increase the risk of transplant failure. This study compares the outcomes from marginal and non-marginal graft transplantation in 103 cases of liver transplantation due to chronic hepatic failure. DESIGN AND SETTING: One hundred and three consecutive liver transplantations to treat chronic liver disease performed in the Liver Transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…Bacchella et al in 2008 suggested a scoring system to denote the liver graft quality including serum levels of transaminases in donors. In their study, liver grafts from donors with AST and/or ALT levels of more than 600 IU/L were routinely discarded (8). Moreover, studies on machine perfusion during the ex vivo phase of preservation, has shown that the level of transaminase in perfusate fluid may predict primary non-function and graft failure (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacchella et al in 2008 suggested a scoring system to denote the liver graft quality including serum levels of transaminases in donors. In their study, liver grafts from donors with AST and/or ALT levels of more than 600 IU/L were routinely discarded (8). Moreover, studies on machine perfusion during the ex vivo phase of preservation, has shown that the level of transaminase in perfusate fluid may predict primary non-function and graft failure (22).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of serum transaminases in donors signify injury to hepatocytes, thus many transplant experts discard livers with markedly elevated levels of serum transaminases for transplantation (1, 7, 8). In spite of this, it is not clear whether high levels of serum transaminases in the donor will affect the allograft function, and there is no clear upper limit in serum transaminases that contraindicates use in transplantation (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported an increase in mortality in liver transplant patients, especially in cases in which the recipients were more seriously ill. (19) …”
Section: Discussionmentioning
confidence: 99%
“…While some authors feel that marginal donor use portends no impact on recipient survival and graft function [10], others feel that especially in high-MELD donors, the risk of early post-transplant mortality is increased with marginal graft use [11]. Many feel that recipient status should be considered in the use of marginal donors, but the majority of publications advocate the use f marginal or extended donor criteria grafts when the o donor quality can be adapted for the proper recipients [12,13].…”
Section: Discussionmentioning
confidence: 99%